Analisis Potensi Sampah Organik untuk Perencanaan Pengomposan: (Studi Kasus: Pasar Anduonohu, Kota Kendari) - Akmal, Akmal; Ndibale, Wa; Sumarlin, Sumarlin (Universitas Muhammadiyah Kendari, 2024)
This research examines the calculation of market waste generation as a material for composting planning. The lack of proper processing of organic waste has resulted in many environmental problems caused by waste, one of which is organic waste. Therefore, this research aims to determine the amount of organic waste generated. The method used in this research is quantitative. The research results show that the amount of organic waste generated at Anduonohu ​​Market is 103.44 Kg/day or the equivalent of 37,755.37 Kg/year. The amount of vegetable waste generated was 39.31 Kg/day or equivalent to 14,347.33 Kg/year and the amount of fruit waste generated was 64.13 Kg/day or equivalent to 23,408.04 Kg/year. The potential for producing compost that can be obtained is 67.24 kg/day. This research can be a reference or example for processing organic waste appropriately and with economic value.